A compound heterozygous mutation in the gene: the first pediatric case causes fish odor syndrome in Korea - Ji Hyun Kim; Sung Min Cho; Jong-Hee Chae (Korean Pediatric Society, 2017)
Trimethylaminuria (TMAuria), known as "fish odor syndrome," is a congenital metabolic disorder characterized by an odor resembling that of rotting fish. This odor is caused by the secretion of trimethylamine (TMA) in the breath, sweat, and body secretions and the excretion of TMA along with urine. TMAuria is an autosomal recessive disorder caused by mutations in flavin-containing monooxygenase 3 (FMO3). Most TMAuria cases are caused by missense mutations, but nonsense mutations have also been reported in these cases. Here, we describe the identification of a novel FMO3 gene mutation in a patient with TMAuria and her family. A 3-year-old girl presented with a strong corporal odor after ingesting fish. Genomic DNA sequence analysis revealed that she had compound heterozygous FMO3 mutations; One mutation was the missense mutation p.Val158Ile in exon 3, and the other was a novel nonsense mutation, p.Ser364X, in exon 7 of the FMO3 gene. Familial genetic analyses showed that the p.Val158Ile mutation was derived from the same allele in the father, and the p.Ser364X mutation was derived from the mother. This is the first description of the p.Ser364X mutation, and the first report of a Korean patient with TMAuria caused by novel compound heterozygous mutations.